Self-Therapy With Social Cohesion Methods For Overcoming Anxiety Disorder - Rakhman, Muhammad Arief (Universitas Pendidikan Indonesia (UPI), 2022)
Anxiety disorder is a mental disorder that has a condition that will shake anxiety and feel worried about something, even though he is in a normal situation. This anxiety disorder is sometimes experienced by students when they develop their soft skills. This study aims to determine whether self- therapy with the method of social cohesion or social cohesion can minimize anxiety disorders experienced by students of Social Studies Education, Universitas Pendidikan Indonesia or not. This research is descriptive qualitative. Instruments used for data collection in the form of interviews, direct observation and literature study. The data collection process was carried out in the environment around the Faculty of Social Science Education, Universitas Pendidikan Indonesia for interviews and in the resource class for observations. From the results of this study, it can be concluded that self-therapy through social cohesion methods to minimize anxiety disorders is quite helpful, although not completely.